2007
DOI: 10.1042/bst0351114
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of T-cell migration by co-stimulatory molecules

Abstract: Migration of primed T-cells to the antigenic site is an essential event in the development of effective immunity. This process is tightly regulated in order to ensure efficient and specific responses. Most studies have focused on non-specific mediators of T-cell migration, including integrins and chemokines. However, recent studies have highlighted the key role of the T-cell receptor and co-stimulatory molecules in guiding T-cell access to antigenic tissue. Here, we review the experimental evidence for an esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The present study suggests that CCR9 and CCR10, the respective chemokine receptors that recruit T and B cells to secondary lymphoid structures in the gut and skin, are not expressed in LF (23)(24)(25).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The present study suggests that CCR9 and CCR10, the respective chemokine receptors that recruit T and B cells to secondary lymphoid structures in the gut and skin, are not expressed in LF (23)(24)(25).…”
Section: Discussionmentioning
confidence: 67%
“…In the present study, we examined the expression of CXCR3 and its ligands by lymphoid follicle cells in the COPD lung and examined the effects of cigarette smoking on lymphoid follicle CXCR3 expression by comparing results obtained in subjects with COPD with smokers without COPD and never-smokers. Finally, because specific chemokine receptors mediate T-cell recruitment into lymphoid follicles in other parts of the body, we examined LF expression of CCR9 and CCR10, the chemokine receptors that mediate T-cell recruitment into lymphoid follicles in the skin (i.e., CCR9) and gut (i.e., CCR10) (23)(24)(25)(26).…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
“…Along these lines, a recent study demonstrate that recruitment of Treg to sites of inflammation is strongly favored by their ability to recognize self-Ags presented by endothelium ( 182 ). Of note, the specific expression patterns of costimulatory/coinhibitory molecules found on endothelium are thought to strongly influence the above processes ( 183 ).…”
Section: Potential Functions Of Endothelial Nhapcmentioning
confidence: 99%
“…Chemokines have been shown to be involved in lymphocyte chemotaxis (6,7), and cause cancer cells to home to specific secondary sites to promote organ-specific metastasis (8,9). It has recently been shown that CXCR4, CXCR7 and CCR7 are expressed by BrCa cells (10-13) and play an important role in metastatic spread of breast tumor cells to the lungs and lymph nodes (5,14).…”
Section: Discussionmentioning
confidence: 99%